2017
DOI: 10.1088/1361-6528/aa8b32
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric pulsed laser deposition and thermal annealing of plasmonic silver nanoparticle films

Abstract: A new method for pulsed laser deposition of plasmonic silver nanoparticle (NP) films in flowing gas at atmospheric pressure is described. The ablation was done using an excimer laser at 248 nm. Fast optical imaging shows that the ablation plume is captured by the flowing gas, and is expected to form a NP aerosol, which is carried 5-20 mm to the substrate. The dependence of the deposition rate on laser fluence, gas flow velocity, and target-substrate distance was investigated using electron microscopy and absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Studies were conducted on DBD as a process to generate active charge species, ozone, and free radicals for biological and medical applications such as sterilization and decontamination of environmental pollutions [ 25 , 26 , 27 ]. Processing particle aerosol with the free gas jet has been reported before and interesting results were reported [ 28 ]. Processing particle aerosols with the DBD plasma in the surface discharge configuration for biocompatible coating is relatively less reported, though recently, atmospheric plasma jets were employed to entrain the particle aerosol for the deposition on a solid surface, and interesting results were reported [ 4 , 15 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies were conducted on DBD as a process to generate active charge species, ozone, and free radicals for biological and medical applications such as sterilization and decontamination of environmental pollutions [ 25 , 26 , 27 ]. Processing particle aerosol with the free gas jet has been reported before and interesting results were reported [ 28 ]. Processing particle aerosols with the DBD plasma in the surface discharge configuration for biocompatible coating is relatively less reported, though recently, atmospheric plasma jets were employed to entrain the particle aerosol for the deposition on a solid surface, and interesting results were reported [ 4 , 15 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nedyalkov et al [23] studied APLD of Au NP films by reducing the target-substrate to 5 mm, and nano-porous films were synthesised. Khan et al [24] showed that by using a jet of Ar gas directed across the ablation target it was possible to deposit silver NP films at up to 20 mm from the target in Ar at atmospheric pressure, and these films were effective for SERS. Cavaliere et al [25] have recently carried out fs-PLD of TiO 2 at ambient pressure and room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…14 Thus for APLD, the density of laser-produced plasma plume is several orders of magnitude higher than encountered for a low-pressure plasma in vacuum or background gas. 24,25 For the typical laser fluence value 1.4 J cm −2 , the plasma plume moves pretty slowly, typically at a velocity of 5 × 10 2 ms −1 compared to 1 to 3 × 10 4 ms −1 in a vacuum. 24 The ablation plume is thus spatially confined and leads to the formation of NPs in the vicinity close to the target surface.…”
Section: Introductionmentioning
confidence: 99%